2021
DOI: 10.5194/bg-18-1009-2021
|View full text |Cite
|
Sign up to set email alerts
|

Subsurface flow and phosphorus dynamics in beech forest hillslopes during sprinkling experiments: how fast is phosphorus replenished?

Abstract: Abstract. The phosphorus (P) concentration of soil solution is of key importance for plant nutrition. During large rainfall events, the P concentration is altered by lateral and vertical subsurface storm flow (SSF) that facilitates P mobilization, redistribution within the soil profile and potential P export from the ecosystem. These processes are not well studied under field conditions. Important factors of the replenishment of P concentrations in soil solutions are the rate of P replenishment (by biotic and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 72 publications
1
13
1
Order By: Relevance
“…Thus, the observed P fluxes during our experiments were in a comparable range of values for annual P loads as in above mentioned studies. With regard to the different considered time intervals, even the tenfold lower value for P fluxes from organic layer which was observed in our few-hours experiment seems to be rather high in comparison to the annual estimates of Rinderer et al (2021). This result can be suspected in the setup of the artificial rain experiments.…”
Section: Site Effect On P Transport Through Preferential Flow Pathwayscontrasting
confidence: 43%
See 2 more Smart Citations
“…Thus, the observed P fluxes during our experiments were in a comparable range of values for annual P loads as in above mentioned studies. With regard to the different considered time intervals, even the tenfold lower value for P fluxes from organic layer which was observed in our few-hours experiment seems to be rather high in comparison to the annual estimates of Rinderer et al (2021). This result can be suspected in the setup of the artificial rain experiments.…”
Section: Site Effect On P Transport Through Preferential Flow Pathwayscontrasting
confidence: 43%
“…Thus, our results strongly support the conceptional idea of a recycling (low-P) system which is able to gain their main nutrient supply from organic layer (cf. Lang et al 2017;Hauenstein et al 2018;Rinderer et al 2021). Bu ¨nemann et al (2016 found biological/biochemical processes to predominantly control TP i,s availability in the low-P-adsorbing sandy soil at the low-P site.…”
Section: Site Effect On P Transport Through Preferential Flow Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite of using an irrigation approach to overcome site and weather variations, the estimated TDP fluxes, ranging between 12 and 60 mg total P m -2 yr -1 across all horizons (Table 3), compare well with the P fluxes measured in other forest ecosystems, 420 ranging from 9 to 62 mg P m -2 yr -1 (Qualls, 2000;Fitzhugh et al, 2001;Hedin et al, 2003;Piirainen et al, 2007;Sohrt et al, 2019;Rinderer et al, 2021). The P fluxes observed here are about one magnitude lower than those determined in a laboratory study with isolated horizons from the same sites (ranging from 70 to 320 mg P m -2 yr -1 across all horizons; Brödlin et al, 2019a).…”
Section: Fluxesmentioning
confidence: 59%
“…Soil solutions were collected over a period of 1.5 hours from the start of the irrigation. The collection represents the "first flush" leaching (Bol et al, 2016;Makowski et al, 2020;Rinderer et al, 2021). The application rate represents maximum rainfall intensities at the study sites.…”
Section: Artificial Irrigation and Samplingmentioning
confidence: 99%